1986
DOI: 10.1136/bjsm.20.3.115
|View full text |Cite
|
Sign up to set email alerts
|

Stress inoculation training to control anxiety in sport: two case studies in squash.

Abstract: This study arose as a result of two squash players, one male one female, seeking advice on how to improve their mental approach to playing. They both felt that their game suffered badly through too much anxiety. After preliminary interviews it was decided to use a programme of stress inoculation training to help them learn to control their anxiety. In order to obtain baseline measures of anxiety, both subjects completed a state anxiety questionnaire on five occasions, immediately prior to playing important lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…To further develop a performer's stress management skills, the findings of the present study could be used to inform the planning and implementation of stress inoculation training (cf. Meichenbaum, ; Mace & Carroll, ). Specifically, this training involves exposing a performer to appropriate and progressively demanding stressors in a supportive and controllable environment so that they can develop resilience and practice his or her stress management.…”
Section: Discussionmentioning
confidence: 99%
“…To further develop a performer's stress management skills, the findings of the present study could be used to inform the planning and implementation of stress inoculation training (cf. Meichenbaum, ; Mace & Carroll, ). Specifically, this training involves exposing a performer to appropriate and progressively demanding stressors in a supportive and controllable environment so that they can develop resilience and practice his or her stress management.…”
Section: Discussionmentioning
confidence: 99%
“…In sports, such approaches have already been demonstrated to be effective to reduce anxiety and increase performance (Hamilton & Fremouw, 1985;Mace & Carroll, 1986, 1989.…”
Section: A Coach Perspective On the Use Of Planned Disruptions In Higmentioning
confidence: 99%
“…Therefore, we expected that activation and emotional control would be relevant to understanding both imagery and self-talk's indirect effects on endurance. Furthermore, the use of imagery and self-talk can serve an affirmatory purpose thus assisting performance by reducing levels of negative thinking (Mace & Carroll, 1986). Previous research has also reported that imagery and ST use can enhance athletes' attentional control (Calmels, Berthoumieux, & D'Arripe-Longueville, 2004;Hatzigeorgiadis et al, 2007) and so could assist to block out irrelevant stimuli, such as pain.…”
Section: Psychological Skills and Endurancementioning
confidence: 99%